A new species of Copa (Araneae: Corinnidae: Castianeirinae) from dry forests in the north west of Madagascar - Pett, Brogan L.; Rabemananjara, Paul Bienvenu (Zootaxa, 2022)
A new species of the castianeirine spider genus Copa Simon, 1885, is described from northwestern Mahamavo region in Madagascar. Copa sakalava sp. nov. (♂♀) is illustrated and diagnosed against continental Afrotropical congeners.